Sustainability measurement in a logistics transportation company - Ferreira, J.; Albuquerque, V.; Pereira, F.; Rocha, J.; Dias, J. (Transportation Research Procedia, 2023)
We present a preliminary study to the Decision Support System for Sustainable Logistics Transportation, using as case study, the Portuguese logistics transportation company Santos e Vale. In the last five years, it has reduced its fleet carbon footprint by 20%. Our research presents a systematic literature review of indicators, carbon footprint models, and reduction measures associated to the sector, using the PRISMA method. Moreover, we considered the application of methodologies and analytical models to measure the logistic transportation carbon footprint, such as in Greenhouse Gas Protocol, ISO 14064 and EN 16258. Our aim is twofold:(1) provision of standard methodologies and analytical models targeting the reduction of carbon footprint in logistics transportation, to a more sustainable operation;(2) future development of a Decision Support System, to assist the monitoring over time.